Novel Suicide Ligands of Tubulin Arrest Cancer Cells in S-Phase - Ashley Davis; Jian-Dong Jiang; Kim M. Middleton; Yue Wang; Imre Weisz; Yi-He Ling; J. George Bekesi (Neoplasia: An International Journal for Oncology Research, 1999)
It is presently accepted that the mechanism of action for all anti-tumor tubulin ligands involves the perturbation of microtubule dynamics during the G2/M phase of cell division and subsequent entry into apoptosis 1]. In this report, we challenge the established dogma by describing a unique mechanism of action caused by a novel series of tubulin ligands, halogenated derivatives of acetamido benzoyl ethyl ester. We have developed a suicide ligand for tubulin, which covalently attaches to the target and shows potent cancericidal activity in tissue culture assays and in animal tumor models. These compounds target early S-phase at the G1/S transition rather than the G2/M phase and mitotic arrest. Bcl-2 phosphorylation, a marker of mitotic microtubule inhibition by other tubulin ligands was dramatically altered, phosphorylation was rapid and biphasic rather than a slow linear event. The halogenated ethyl ester series of derivatives thus constitute a unique set of tubulin ligands which induce a novel mechanism of apoptosis.